Pengaruh Penerapan Akuntansi Pemerintahan dan Pengendalian Internal Terhadap Good Governance (Studi Kasus pada Dinas Kesehatan dan Dinas Kependudukan dan Catatan Sipil Kabupaten Kerinci) - Zachari Abdallah; Teti Ramadhani (Journal on Education, 2022)
The purpose of this study was to determine the effect of implementing government accounting and internal control on good governance (case studies in the health office and the Kerinci district population and records office). Data were collected from questionnaires given to 22 employees of the Kerinci District Health Office and Population and Civil Registry Service. Data analysis was carried out using multiple regression analysis through the SPSS Version 20 program. The results showed that the Application of Government Accounting and Internal Control had an effect on Good Govarnance (Case Study at the Health Office and the Kerinci Regency Population and Civil Registry Office), this is evidenced by t count > t table (2.975 > 2.08596). Internal control has a significant effect on good governance (case study at the Health Office and the Kerinci Regency Population and Civil Registry Service), as evidenced by t count > t table (3.059 > 2.08596). Simultaneously there is a significant influence between the Application of Government Accounting and Internal Control on Good Govarnance (Case Study at the Health Office and the Kerinci Regency Population and Civil Registry Office), which can be proven by F count > F table (9.949 > 3.52). The effect of the application of government accounting and internal control on good governance (a case study in the health office and the population and civil registration office in Kerinci district) is 51.2%, the remaining 48.8% is explained by other causative factors not examined in this study.